Olive Kitteridge - Strout, Elizabeth (Scribner, 2016)
At the edge of the continent, in the small town of Crosby, Maine, lives Olive Kitteridge, a retired schoolteacher who deplores the changes in her town and in the world at large but doesn't always recognize the changes in those around her.